Effectiveness and safety of a newly designed self-assembling gel in the treatment of endoscopic submucosal dissection-induced gastric ulcer: A multicenter randomized controlled trial - Meng Li; Xiaoliang Jin; Xinxin Zhou; Guochun Lou; Feng Ji; Liangjing Wang; Haifeng Jin; Xuan Huang; Jing Zhao; Haibiao Bao; Liang Huang; Changpei Shi; et al. (Frontiers Media S.A., 2022)
Objectives: To evaluate the effectiveness and safety of a newly designed self-assembling gel in treating ESD-induced gastric ulcers in patients.Methods: This open-label, multicenter, randomized controlled trial enrolled patients who underwent ESD between September 2020 and May 2021. Patients were randomized (1:1) to receive the gel (applied to cover the entire ulcer bed under endoscopic guidance immediately after ESD; gel group) or not (control group). The primary outcome was the ulcer healing rate at 28 days. And the secondary outcomes were the delayed bleeding, changes in the ulcer stage, and adverse events.Results: Finally, 125 patients (mean age, 63.7 years; 70 [56.0%] males) were enrolled. The ulcer healing rate was higher in the gel group than in the control group at 28 days (96.9 ± 4.1% vs. 94.7 ± 5.0%; p = 0.001). The ulcer reduction rate at 28 days differed significantly (p < 0.001) between ulcers with majority gel coverage (99.8%), ulcers with minority gel coverage (96.2%), and ulcers with no gel coverage (98.0%). Delayed bleeding was found in 1/63 gel-treated patients (1.6%) versus 5/62 controls (8.1%). A1-stage ulcers were found in 16/63 patients in the gel group versus 44/62 patients in the control group (25.4% vs. 71.0%, p < 0.001) at 3-5 days.Conclusion: The newly developed self-assembling gel was safe and effective in accelerating gastric ulcer healing in patients after ESD.Clinical Trial Registration: UMIN Clinical Trials Registry System (registration number, ChiCTR2100052935).